ANALISIS PENGARUH LEVERAGE, UKURAN PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Nurus Sya’ah, 13.05.52.0238; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2017)
The purpose of this researchis to analyze the effect ofÂ leverage, company size, and corporate governance to the earnings management on manufacturing companies listed in Indonesia Stock Exchange 2011-2016 period.Data used in this research is secondary data, the data in this study were obtained from the Financial Statements, Annual Report, ICMD (Indonesian Capital Market Directory) 2011-2016. The sampling method used is purposive sampling. The amount of data that is processed as many as 126 companies. The results of this study indicate that the leverage, company size, managerial ownership, audit quality, and audit committee has no coefisien effect on earnings management. Keywords: Earnings Management, Leverage, Company Size, Managerial Ownership, Audit Quality, Audit Committee